2002
DOI: 10.1108/02686900210444798
|View full text |Cite
|
Sign up to set email alerts
|

Implications of non‐financial performance measures in Finnish banks

Abstract: The inadequacies of traditional management accounting (MA) information indicate a need for management to find proper measuring tools for emerging non‐financial performance (NFP) in the highly competitive financial services, as well as in the manufacturing industry. Thus, the role of MA in measuring the performances of emerging NFP has been receiving increased emphasis in the increasingly important service industries. Considering the shortcomings of the traditional MA information system, particularly the measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Vivas, Pastor, and Hasan (2001) examined the performances of banks in the countries of the European Union and the impacts of environmental factors on performance. Krishnan, Ramaswamy, and Damien (1999) Hussain, Gunasekaran, and Islam (2002) stated that the concept of customer satisfaction was the most important indicator of bank performances. Sherman and Gold (1985) and Oral and Yolalan (1990) stated that financial rates alone were not sufficient as performance criteria and indicated that with such a performance evaluation, it would not be possible to make long-term evaluations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Vivas, Pastor, and Hasan (2001) examined the performances of banks in the countries of the European Union and the impacts of environmental factors on performance. Krishnan, Ramaswamy, and Damien (1999) Hussain, Gunasekaran, and Islam (2002) stated that the concept of customer satisfaction was the most important indicator of bank performances. Sherman and Gold (1985) and Oral and Yolalan (1990) stated that financial rates alone were not sufficient as performance criteria and indicated that with such a performance evaluation, it would not be possible to make long-term evaluations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Short-and long-term strategies bringing the company into better condition will be published concurrently with the company's annual report. Non-financial information studied for its relationship to the company performance will result in some authentications, indicating that non-financial measure has significant relationship to the future company performance (Banker, et al,2000;Ittner, et al, 2003;Hussain, et al,2002). Based on the statement above, the following hypotheses can be formulated.…”
Section: Investor Decisionmentioning
confidence: 99%
“…Not only that, the financial performance measures are characterized by difficulty in acquiring objective data because organizations (mostly private companies) are normally unwilling to provide its correct data to the public. Financial measures face the challenge of overcoming the criticism that it is one-dimensional and thus, it offers limited services (Hussain, Gunasekaran, and Islam 2002).…”
Section: The Concept Of Small and Medium Scale Industrymentioning
confidence: 99%